(untitled) (Journal of Comparative & International Higher Education, 2023)
In every university’s endeavor to promote internationalization, pedagogy is vital and there is a need to research internationalization at different pedagogical levels within different learning approaches (Katsara & De Witte, 2020). This paper discusses the value of implementing culturally responsive pedagogy (CRP) within the teaching context of Problem-Based Learning (PBL). By means of a critical review, it is revealed that little is known on specific classroom internationalized pedagogies, for example PBL appears difficult to be implemented in a uniform way across the globe while becoming culturally responsive during teaching seems quite personal. Some future lines of research on students’ support to PBL learning within teaching are offered providing the rationale for the development of possible departmental CRP training sessions for teachers. The evaluation of such training is suggested to determine the extent to which such an initiative could be part of a departmental pedagogy of internationalization policy development at micro level. Key words: culturally responsive pedagogy, problem-based learning, internationalization, higher education